Role of document management system for business processes optimization - Orlov, I.V. (Problems of Theory and Methodology of Accounting, Control and Analysis, 2024)
The automation of work processes and seamless integration with various business services highlight the essential role of digital document management systems (DMS) in enhancing organizational flexibility, productivity, and adaptability. DMS serve as centralized repositories that streamline, automate, and interconnect business processes, thereby facilitating effective document management. The integration of DMS with Enterprise Resource Planning (ERP) systems provides a comprehensive solution for optimizing business workflows, addressing the needs for both operational efficiency and strategic management. The research paper delineates a business model for the life cycle management of electronic documents and records, focusing on the integration of processes such as document creation, management, approval, and secure distribution. This integrated approach enhances organizational structure, optimizes processes, and bolsters security, leading to significant cost reductions and increased work efficiency. The model emphasizes the importance of streamlined and automated document workflows in reducing manual errors and operational bottlenecks. Key features of DMS include advanced mechanisms for digitizing physical documents, ensuring that all data is captured accurately and efficiently. Centralized storage with version control allows for easy retrieval and management of documents, ensuring that the latest versions are always accessible. Additionally, advanced search and accessibility features enable quick and efficient document retrieval, which is crucial for maintaining high productivity levels. The study underscores the pivotal role of DMS in modern enterprises, advocating their implementation as a strategic move to drive operational excellence and competitive advantage. By integrating DMS with ERP systems, businesses can achieve a cohesive and efficient operational environment that supports both day-to-day activities and long-term strategic goals. This comprehensive approach to document management not only optimizes efficiency and reduces errors but also enhances the overall agility and responsiveness of the organization in a rapidly changing economic environment.